Bioequivalence study of fluticasone propionate nebuliser suspensions in healthy Chinese subjects - Cheng, Feng; Shen, Tao; Zhang, Fucheng; Lei, Chenghao; Zhu, Ye; Luo, GuoJun; Xiao, Dawei (Frontiers in Pharmacology, 2025)
BackgroundFluticasone propionate is a synthetic trifluoro-substituted glucocorticoid, a highly selective glucocorticoid receptor agonist. Fluticasone propionate nebuliser suspensions is an inhaled corticosteroid with the low systemic bioavailability which provides a low risk (benefit outcome without the adverse effects that accompany systemically administered corticosteroids), referred as a first-line preventive agent for patients with persistent asthma. China has become one of the countries with the highest asthma mortality rate in the world in the past years. It urgently needs good generic drugs to help ease patients’ burden and improve their quality of life.ObjectiveThe primary objective of this study was to evaluate the bioequivalence of fluticasone propionate nebuliser suspensions between test formulation (generic product) and reference formulation (original product, Flixotide Nebules®) with the pharmacokinetic parameters as the endpoint indicators and the secondary objective was to evaluate the safety of two inhalated fluticasone propionate nebuliser suspensions under the condition of fasting in healthy Chinese subjects.MethodsThe bioequivalence study was conducted with a single-center, randomized, open-label, single-dose, two sequences, two-period crossover design. 24 healthy subjects were randomly assigned into T-R and R-T sequence groups with 12 patients in each group. The subjects were administered 1 mg (2 mL:0.5 mg,plastic ampoules) of generic fluticasone propionate nebuliser suspension as a test formulation or Flixotide Nebules® as reference formulation and cross administration after sufficient washout period (5 days) for the second period study. The blood sample was collected at predetermined time points up to 48 h and the plasma concentration of fluticasone propionate was determined by HPLC-MS/MS in healthy subjects after inhalation of test or reference formulation. The non-compartment model method (NCA module) of the WinNonlin® software (version 8.3) was used to calculate the pharmacokinetic parameters (Cmax, AUC0-t, AUC0-∞) between the test formulation and the reference formulation were within the predefined range of 80.00% and 125.00%, bioequivalence of both formulations was demonstrated.ResultsThe 90% confidence intervals of the T/R ratio of the geometric mean of Cmax, AUC0-t, and AUC0-∞ for both formulations were 90.24%–112.68%, 96.99%–112.27% and 96.41%–111.59% respectively, which were all within the bioequivalent range of 80%–125%. No severe, suspicious or unexpected serious adverse reactions were reported.ConclusionThe test and reference formulations of fluticasone propionate nebuliser suspension were pharmacokinetic bioequivalent and were well tolerated and safe in all subjects.